B64. Right Ventricle in Pulmonary Vascular Disease 2012
DOI: 10.1164/ajrccm-conference.2012.185.1_meetingabstracts.a3446
|View full text |Cite
|
Sign up to set email alerts
|

Von Willebrand Factor And The Right Ventricle: The MESA-Right Ventricle Study

Abstract: Elevation in plasma activity of von Willebrand Factor (vWF) reflects endothelial dysfunction and predicts death in pulmonary arterial hypertension (PAH). Higher vWF activity is also associated with lower right ventricular (RV) ejection fraction in PAH. Little is known about the relationship between vWF and RV structure and function in adults without cardiovascular disease. In the current investigation, we included 1,976 participants with MRI assessment of RV structure and function and measurement of vWF activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Covariables including age, sex, race/ ethnicity, height, weight, education, income, presence of hypertension or diabetes mellitus, fasting plasma glucose, cholesterol, systolic blood pressure, smoking status and pack-years, percent emphysema (obtained by chest computed tomography), and selfreported lung disease (asthma and/or emphysema) were measured as previously described (23). Because levels of air pollution within a neighborhood are correlated over time, self-reported time a participant lived in the index neighborhood (the residential neighborhood used to determine 1-year pollutant estimates) was used as a surrogate for exposure duration (8).…”
Section: Covariablesmentioning
confidence: 99%
“…Covariables including age, sex, race/ ethnicity, height, weight, education, income, presence of hypertension or diabetes mellitus, fasting plasma glucose, cholesterol, systolic blood pressure, smoking status and pack-years, percent emphysema (obtained by chest computed tomography), and selfreported lung disease (asthma and/or emphysema) were measured as previously described (23). Because levels of air pollution within a neighborhood are correlated over time, self-reported time a participant lived in the index neighborhood (the residential neighborhood used to determine 1-year pollutant estimates) was used as a surrogate for exposure duration (8).…”
Section: Covariablesmentioning
confidence: 99%
“…Other covariables, including race/ethnicity, height, weight, presence of hypertension or diabetes mellitus, C-reactive protein (CRP), smoking status, spirometry, and emphysema, were measured as described elsewhere (see appendix, available online). 24…”
Section: Biomarkers and Covariablesmentioning
confidence: 99%
“…We hypothesized that H2RA use would be independently associated with lower RV mass and smaller RV end-diastolic volume (RVEDV). Some of the results of these studies have been previously reported in the form of an abstract (13).…”
mentioning
confidence: 96%